Using Entropy and Linear Exponential Loos Function Estimators the Parameter and Reliability Function of Inverse Rayleigh Distribution - Ali Abod, Masooma; Mansoor Gorgees, Hazim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
This paper is devoted to compare the performance of non-Bayesian estimators represented by the Maximum likelihood estimator of the scale parameter and reliability function of inverse Rayleigh distribution with Bayesian estimators obtained under two types of loss function specifically; the linear, exponential (LINEX) loss function and Entropy loss function, taking into consideration the informative and non-informative priors. The  performance of such estimators assessed on the basis of mean square error (MSE) criterion. The Monte Carlo simulation experiments are conducted in order to obtain the required results.